2008
DOI: 10.1080/14622200802443494
|View full text |Cite
|
Sign up to set email alerts
|

A smoking cessation intervention plus proactive quitline referral in the pediatric emergency department: A pilot study

Abstract: The prevalence of adult tobacco users who utilize the emergency department as patients or parents is disproportionately higher than the national average rates of tobacco use. Thus, it is advised that the emergency department be utilized as a venue for providing tobacco cessation counseling to adult tobacco users. Using a randomized control trial design, this pilot study evaluated the effect of a brief tobacco cessation intervention for tobacco using parents of children brought to a pediatric emergency departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 27 publications
4
60
2
1
Order By: Relevance
“…Several other studies involving the pediatrician as counselor have been done, though these were either underpowered or plagued by loss to follow-up [14,[17][18][19]. Despite these limitations, each reported significant parental willingness to receive cessation counseling by a pediatrician and trends toward more successful cessation in the intervention groups.…”
Section: Smoking Cessation Counseling For Parents In the Pediatric Sementioning
confidence: 95%
See 4 more Smart Citations
“…Several other studies involving the pediatrician as counselor have been done, though these were either underpowered or plagued by loss to follow-up [14,[17][18][19]. Despite these limitations, each reported significant parental willingness to receive cessation counseling by a pediatrician and trends toward more successful cessation in the intervention groups.…”
Section: Smoking Cessation Counseling For Parents In the Pediatric Sementioning
confidence: 95%
“…There were some statistically significant impacts reported in these small studies. In one randomized, controlled trial of a brief intervention in an emergency department setting, 59% of the intervention group vs. 34% of the control group (p <0.01) reported attempting to quit at 3 months post-intervention [18]. Also, a small German study reported a significant decrease in number of cigarettes smoked and cotinine levels after a brief, office based intervention, though it was not a controlled trial [17].…”
Section: Smoking Cessation Counseling For Parents In the Pediatric Sementioning
confidence: 96%
See 3 more Smart Citations